IMPLEMENTASI PROGRAM MBKM MENGAJAR MATERI PERSAMAAN DASAR AKUNTANSI DAN JURNAL PERUSAHAAN JASA DI TARSISIUS 1 - Riyanti Teresa; Chelsya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
The Merdeka Belajar Kampus Merdeka (MBKM) Program provides opportunities for university students to teach outside the campus, one of which is through accounting extracurricular activities at SMA Tarsisius 1 Jakarta. The partner’s main problem lies in the students’ low understanding of basic accounting concepts and the lack of practical learning activities outside formal classroom sessions. Over a period of four months, the author taught students from grades X to XII with core materials covering the basic accounting equation, journal entries, and simple financial statements for service companies. The teaching materials were prepared by the student instructor based on applicable guidelines and adapted to the students’ level of understanding. The learning process was carried out interactively through discussions, quizzes, exercises, and educational games designed to help students comprehend accounting concepts in a more practical manner. Initially, grade X and XI students encountered difficulties in understanding the fundamentals of accounting, particularly in recording transactions, but over time improvement was observed through active participation and better exercise results. Guidance from supervising lecturers also contributed to refining the teaching methods and strategies. This program not only helped students gain a more applicable understanding of accounting but also served as a valuable opportunity for the student instructor to develop teaching skills and communication within the school environment. The results of this activity indicate that the right approach in extracurricular learning can effectively increase students’ interest and literacy in accounting from an early stage. The methods implemented in the teaching assistance at the educational institution include: 1) material planning and preparation, 2) implementation through teaching sessions and exercise discussions, 3) final evaluation through quizzes, and 4) dissemination of results through scientific meetings, final reports, synopses, posters, and intellectual property registration. Program Merdeka Belajar Kampus Merdeka (MBKM) memberikan kesempatan bagi mahasiswa untuk mengajar di luar kampus, salah satunya melalui kegiatan ekstrakurikuler akuntansi di SMA Tarsisius 1 Jakarta. Permasalahan yang dihadapi mitra yaitu rendahnya pemahaman siswa terhadap konsep dasar akuntansi serta kurangnya kegiatan pembelajaran yang bersifat praktis di luar jam pelajaran formal. Selama empat bulan, penulis mengajar siswa kelas X hingga XII dengan materi utama mencakup persamaan dasar akuntansi, pencatatan jurnal, hingga laporan keuangan sederhana pada perusahaan jasa. Materi disusun oleh mahasiswa dengan mengacu pada ketentuan yang berlaku, lalu disesuaikan dengan tingkat pemahaman siswa. Proses pembelajaran dilakukan secara interaktif melalui diskusi, kuis, latihan soal, dan permainan edukatif yang bertujuan membantu siswa memahami konsep akuntansi secara lebih praktis. Pada awalnya, siswa kelas X dan XI mengalami kesulitan memahami dasar-dasar akuntansi, terutama dalam pencatatan transaksi, namun seiring waktu terlihat peningkatan melalui partisipasi aktif dan hasil latihan yang membaik. Bimbingan dari dosen pendamping turut membantu dalam penyempurnaan metode dan strategi pengajaran. Program ini tidak hanya membantu siswa memahami akuntansi secara aplikatif, tetapi juga menjadi sarana bagi mahasiswa untuk mengembangkan keterampilan mengajar dan komunikasi di lingkungan sekolah. Hasil kegiatan menunjukkan bahwa pendekatan yang tepat dalam kegiatan ekstrakurikuler mampu meningkatkan minat serta literasi siswa di bidang akuntansi sejak dini. Metode yang diterapkan dalam asistensi mengajar di satuan pendidikan adalah: 1) Perencanaan dan persiapan materi, 2) Pelaksanaan dengan metode pengajaran dan pembahasan latihan soal, 3) Evaluasi hasil akhir dengan kuis, 4) Publikasi hasil artikel melalui temu ilmiah, laporan akhir, sinopsis, poster, dan HKI.